Tinjauan Yuridis Terhadap Bentuk Perikatan Para Pihak Dalam Sewa Menyewa Rusunawa Di Surakarta - Dinata, Hirza Arsyad Alam; , Shalman Al-Farizi, S.E., S.H, M.Kn (2016)
Development of rental flats in Surakarta of course can also result opening green urban space so that be mre relieved and in this also can help the rejuvenation of city, so the day then the area dirty diminish and them became area is neat, clean, and regular. The rental flats consists of two part that is private flats and rental flats, their terms of adminitration that must be met in lease rental flats, so the government building flats to people who have not been able to have home in way of rent it. Renting rental flats of course has limitations and prohibitions, especially the limited time that must be of candidate tenant or another occupant, their rights and obligations of each. If the occupants does not comply with these regulations then the manager would sanction. There also violation committed a occupant rental flats and the infringement settlement made by manager.